Return-to-play considerations following a COVID-19 infection in elite athletes - Ross, R.; Irvin, L.; Severin, R.; Ellis, B. (Journal of Athletic Training, 2021)
The COVID-19 pandemic has created a unique challenge for sports medicine staffs as they are attempting to safely transition elite athletes into sport participation after a COVID-19 infection. Athletes must isolate for a period of time after testing positive for COVID-19 to prevent the spread of the virus within a community. After an isolation period, a battery of cardiac tests must be given to assess whether or not an athlete is ready to begin a reconditioning protocol. A return-to-play plan should be established to safely re-integrate high-level athletes into strength and conditioning, sport-specific drill work, and contact drill work. Elite athletes should also be gradually eased back into full training loads in order to avoid increases in orthopedic injuries after a prolonged absence from training.